The little mermaid. (Leicestershire, UK : Ladybird Books Ltd)
When King Triton, ruler of the seas tries to stop his daughter Ariel marrying a human prince, she asks the wicked Sea-Witch Ursula to help her. But Ursula has plans of her own. . .
Keywords: Mermaids-stories; Mermaids-Fiction